2000
DOI: 10.5551/jat1994.6.22
|View full text |Cite
|
Sign up to set email alerts
|

Apotipoprotein E Accelerates the Efflux of Cholesterol from Macrophages : Mechanism of Xanthoma Formation in Apolipoprotein E Deficiency

Abstract: A patient with congenitally deficient apolipoprotein (apo) E showed numerous tuberoerutive, tendon xanthomas and severe atherosclerosis, despite a low LDL concentration.In order to study the mechanism of xanthoma formation observed in apo E-deficient patients, we evaluated the effect of VLDL and HDL from the patient on cholesterol ester (CE) accumulation in macrophages.The results showed that there was no difference in CE formation in macrophages among normal VLDL, the patient's VLDL and apo E containing VLDL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In addition, apoE is involved in both the assembly [13,14] and secretion [15,16] of very low-density lipoproteins (VLDLs) in hepatocytes. In macrophages, apoE also plays a critical role in cholesterol efflux [17][18][19][20]. Based on the multiple and critical roles for apoE in the metabolism of lipids and lipoproteins, we and others hypothesized and showed that a fraction of apoE internalized with lipoproteins escapes lysosomal degradation and is resecreted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, apoE is involved in both the assembly [13,14] and secretion [15,16] of very low-density lipoproteins (VLDLs) in hepatocytes. In macrophages, apoE also plays a critical role in cholesterol efflux [17][18][19][20]. Based on the multiple and critical roles for apoE in the metabolism of lipids and lipoproteins, we and others hypothesized and showed that a fraction of apoE internalized with lipoproteins escapes lysosomal degradation and is resecreted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is involved in both the assembly (13,14) and secretion (15,16) of VLDL. ApoE also plays a critical role in cholesterol efflux from macrophages (17)(18)(19)(20), a role that could be attributable to both intracellular and extracellular effects. Because apoE can easily transfer between lipoproteins and yet binds tightly to its receptors, we first hypothesized and later demonstrated that a substantial amount of internalized apoE escapes lysosomal degradation and is routed back (recycled) through the secretory pathway (21)(22)(23).…”
mentioning
confidence: 99%
“…In addition, it is involved in both the assembly (13,14) and secretion (15,16) of VLDLs. ApoE also plays a critical role in cholesterol efflux from macrophages (17)(18)(19)(20), a role that could be due to both intracellular and extracellular effects. Because apoE can easily transfer between lipoproteins and binds tightly to its receptors, we and others hypothesized and proved that a substantial amount of internalized apoE escapes lysosomal degradation and is routed into the secretory pathway.…”
mentioning
confidence: 99%